2019
DOI: 10.1534/genetics.118.301853
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and Maintenance of Chromatin Architecture Are Promoted Independently of Transcription by the Histone Chaperone FACT and H3-K56 Acetylation in Saccharomyces cerevisiae

Abstract: FACT (FAcilitates Chromatin Transcription/Transactions) is a histone chaperone that can destabilize or assemble nucleosomes. Acetylation of histone H3-K56 weakens a histone-DNA contact that is central to FACT activity, suggesting that this modification could affect FACT functions. We tested this by asking how mutations of H3-K56 and FACT affect nucleosome reorganization activity in vitro, and chromatin integrity and transcript output in vivo. Mimics of unacetylated or permanently acetylated H3-K56 had differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 81 publications
4
29
0
Order By: Relevance
“…Blue, red and green lines indicate relative nucleosome enrichment as determined by H3 ChIP after 0, 20 and 40 min post arrest, respectively. Enrichment peaks indicate the midpoints of nucleosome positions, and determined nucleosome locations are represented below by circles with two diagonal lines, in agreement with previous work ( 12 , 57 ). Swi5 binding sites are indicated by blue rectangular boxes and determined NDRs are indicated by arrows.…”
Section: Resultssupporting
confidence: 90%
“…Blue, red and green lines indicate relative nucleosome enrichment as determined by H3 ChIP after 0, 20 and 40 min post arrest, respectively. Enrichment peaks indicate the midpoints of nucleosome positions, and determined nucleosome locations are represented below by circles with two diagonal lines, in agreement with previous work ( 12 , 57 ). Swi5 binding sites are indicated by blue rectangular boxes and determined NDRs are indicated by arrows.…”
Section: Resultssupporting
confidence: 90%
“…4). Recently, an involvement of FACT in chromatin architecture independent of transcription has been proposed 36 , our data suggests that this function might be related to cohesin's role in genome architecture. We speculate that similar to its roles in transcription and replication, FACT function as a histone chaperone is likely to occur through destabilization of core nucleosomal particles, to allow movement of cohesins on chromatin.…”
Section: Mainsupporting
confidence: 60%
“…Indeed, it was suggested that the ongoing cryptic transcription in the spt16 mutant leads to histone loss in S. cerevisiae (Feng et al, 2016). Our results cannot exclude the possibility that the +1 nucleosome has an antisense barrier function (McCullough et al, 2019) and that FACT is important for the establishment of this barrier.…”
Section: Transcriptional Alterations Correlate With Nucleosome Densitmentioning
confidence: 63%